2012
DOI: 10.1002/jbt.21453
|View full text |Cite
|
Sign up to set email alerts
|

Genes of Innate Immunity and the Biological Response to Inhaled Ozone

Abstract: Ambient ozone has a significant impact on human health. We have made considerable progress in understanding the fundamental mechanisms that regulate the biological response to ozone. It is increasingly clear that genes of innate immunity play a central role in both infectious and non-infectious lung disease. The biological response to ambient ozone provides a clinically relevant environmental exposure that allows us to better understand the role of innate immunity in non-infectious airways disease. In this bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 163 publications
(206 reference statements)
1
18
0
Order By: Relevance
“…Previous studies found that the estimated level of O 3 from air quality monitors was a poor proxy for personal exposure, because O 3 can react with other pollutants in the ambient environment, especially in the urban area 3031 In experimental studies, O 3 exposure in human alveolar macrophages was linked to decreased phagocytosis and impaired antimicrobial host defence 3233 The exact relation between O 3 and TB requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that the estimated level of O 3 from air quality monitors was a poor proxy for personal exposure, because O 3 can react with other pollutants in the ambient environment, especially in the urban area 3031 In experimental studies, O 3 exposure in human alveolar macrophages was linked to decreased phagocytosis and impaired antimicrobial host defence 3233 The exact relation between O 3 and TB requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In a recently published review by Li et al (2013), the authors describe various events in the airways that can lead to an inflammatory response in the lung. In our work we looked at one aspect of this inflammatory response – the production of cytokines – by measuring the relative expression of genes associated with inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…These multifactorial characteristics make difficult to underline the exact mechanism of PM-induced respiratory adverse effects. However, several in vitro studies have suggested different cell mechanisms associated to certain PM constituents such as: 1) bacterial ENX may be responsible for the inflammatory response due to the activation of Toll-like receptor-4 (TLR4) and transcription factors (e.g., NF-kB) and the release of pro-inflammatory cytokines (e.g., IL-6 and IL-8); 2) TMET [e.g., aluminum (Al), arsenic (As), iron (Fe), cadmium (Cd), copper (Cu), nickel (Ni), mercury (Hg), lead (Pb) and vanadium (V)] may cause cellular lipids, proteins and DNA damage, mutagenicity and carcinogenicity by generating reactive oxygen species (ROS); 3) PAH may cause oxidative stress, aberrant changes in cell cycling, gene expression and DNA functions by generating toxic metabolites due to the activation of aryl hydrocarbon (Ah) receptors and induction of Phase I and II metabolizing enzymes; and 4) air pollutants such as nitro-, sulfurand oxygen-elements (e.g., NO 2 , SO 2 , H 2 S, O 3 ) may cause lung epithelial cell damage, oxidative cellular stress and carcinogenicity [3, 25-26,29,34,37-47]. Based on these and other published studies (Aust et al, 2002; Wang et al, 2013), inflammatory injury and oxidative damage are considered as common mechanisms of PM-induced health adverse effects.…”
Section: Introductionmentioning
confidence: 99%